FATIGUE FAILURE ON DRILLING PIPE THREAD: A CASE STUDY ON DRILL PIPE SS105 - Apriansyah Apriansyah; Hendri Chandra; Diah Kusuma Pratiwi; Aneka Firdaus (Indonesian Journal of Engineering and Science (IJES), 2020)
This study presents a case study investigation on failure analysis of drill pipe during the drilling operation and to establish a general understanding of fatigue failure with experiments and several tests. Drill pipe load comprises tensile, compression, bending, hydrostatic pressure and vibration, which causes damage due to fatigue failure to the drill pipe. The method involves subjecting a 2 in length and nominal diameter 3.25 in connection NC50 19.5 ppf drill pipe to predetermined caused failure by experimental tests and analysis. Mechanical examination such as tensile test and hardness test, and metallurgical examination such as spectrometry, fractography, SEM and EDX testing are conducted. The result shows that the cause of failure on the thread drill pipe was due to fatigue failure. It showed by the presence of microcracks, which accumulated from the load in the drill pipe. In addition, propagation of the crack at critical depth resulting in failure during drilling operations.